The Catherwood Project : Incidents of Visual Reconstructions and Other Matters - Lerner, Jesse (Book collections on Project MUSE., 2017)
The work of Argentine photographer Leandro Katz is presented here in dialogue with the nineteenth-century artist Frederick Catherwood, whose images of Maya ruins have fascinated viewers for more than a century.